THE SCIENTIFIC LITERACY PERFORMANCE OF GIFTED YOUNG SCIENTIST CANDIDATES IN THE DIGITAL AGE - Fausan, Muhammad Mifta; Susilo, Herawati; Gofur, Abdul; Sueb, Sueb; Yusop, Farrah Dina (LPMPP Universitas Negeri Yogyakarta, 2021)
Scientific Literacy (SL) is an important competency to deal with and keep up with the increasingly sophisticated technological developments. However, information about the SL of prospective gifted young scientists over 15 years old has not been widely revealed holistically. Therefore, this survey research aimed to investigate the SL performance of prospective gifted young scientists holistically and compare the SL performance based on the grade level. A total of 278 students from a public senior high school in Jombang Regency, East Java Province, Indonesia, participated in this research. They were asked to take the SL test with 18 essential question items. As a result, the participants still showed low SL performance (total success rate = 40). The one-way ANOVA test results indicated no significant difference in the participants' SL performance based on the grade level. Therefore, three recommendations were provided: teachers should use various learning models, SL should be an explicit focus in science and non-science classrooms, and schools need to be equipped with supporting facilities to accommodate student readiness to practice SL.